Hemophagocytosis in bone marrow aspirates: An indication of hidden pathologies - Sampath Kolavadi Srinivasagowda; Venkatesan Somasundaram; Vinu Balraam; Reena Bharadwaj (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2019)
Background and Objectives: Hemophagocytosis in bone marrow aspirates is fairly common and can be observed in a spectrum of clinical conditions. This study aimed at evaluating the clinicopathological profile of patients showing hemophagocytosis on bone marrow aspirates examined for varied clinical indications. Materials and Methods: In this study, all those bone marrow aspirate smears sent with various clinical indications and which showed hemophagocytosis were included. Finally, 25 bone marrow aspirates were studied. Results: Of 25 patients, 18 (72%) were males and 7 (28%) were females. The age of the patients ranged from 2 to 73 years. Two common clinical indications with which bone marrow aspirates were sent were fever of unknown origin 10 (40%) and HIV-positive patients with cytopenias 7 (24%). Anemia was the most common cytopenias observed followed by cytopenias in other combinations. Microcytic hypochromic anemia was the common morphological type of the anemia encountered in these patients 17 (68%). Twenty-three (92%) of the bone marrow aspirates showed cellular bone marrow with features of hemophagocytosis. Bone marrow aspirate from a HIV-positive patient showed erythroid hyperplasia (78% early erythroids) with giant erythroblasts and features suggestive of parvovirus B19 infection and hemophagocytosis. Conclusions: Hemophagocytosis in the bone marrow aspirates should not be overlooked and always be documented and reported. The presence of hemophagocytosis may be the only clue to the underlying conditions such as systemic infections or hemophagocytic lymphohistiocytosis (HLH). It is therefore recommended that every case which shows hemophagocytosis needs to be reported and further workup be done to confirm the diagnosis of HLH.